Effect of coupling agent on nano-ZnO modification and antibacterial activity of ZnO/HDPE nanocomposite films. Issue 1 (June 2015) - Li, Y N; Xu, W M; Zhang, G Q
Abstract: Commercial zinc oxide nanoparticles were modified by silane coupling agent of KH550 and KH560, respectively. The obtained nanocomposite was characterized by scanning electron microscopy (SEM), Thermogravimetric analyses (TGA) and apparent sedimentation stability (Sapp). Then, nano-ZnO/high-density polyethylene (HDPE) composite films were prepared via melt blending and a hot compression-molding process. The antibacterial testing of the films against E. coli and S. aureus was carried out via plate counting. SEM, TGA and Sapp suggest the modifier of silane changed the surface hydrophilicity and effectively broke the agglomerations of nanoparticles. Antibacterial testing results indicated the antibacterial rate of the films increased with increasing nano-ZnO content. At a low doped content of 0.2 wt%, the types of coupling agent influenced the antibacterial property with that of KH560-modified nano-ZnO/HDPE KH550-modified nano-ZnO/HDPE unmodified nano-ZnO/HDPE films. When the dosage nano-ZnO was over 0.2 wt%, the differences of antibacterial activity resulted by modification was concealed by the strong antibacterial activity with near 100% of the nano- ZnO/HDPE composite films.